2017
DOI: 10.2169/internalmedicine.56.8087
|View full text |Cite
|
Sign up to set email alerts
|

Acute Acalculous Cholecystitis Caused by <i>Giardia lamblia</i>

Abstract: We report a case of a 70-year-old man with acute acalculous cholecystitis caused by Giardia lamblia. Contrast-enhanced computed tomography (CT) showed distention of the gallbladder due to a pericholecystic abscess without gallstones. Magnetic resonance cholangiopancreatography and drip infusion cholecystocholangiography-CT demonstrated a stricture of the hilar bile duct and cystic duct obstruction. We conducted transpapillary bile duct brush cytology and a biopsy of the hilar bile duct stricture; numerous acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
9
1
5
Order By: Relevance
“…He underwent a simultaneous cholecystectomy and elective revascularization of his aortic and visceral occlusive disease. Other case reports present instances of acute acalculous cholecystitis in patients with critical illness causing systemic inflammation such as a severe infection, systemic lupus erythematosus, or burns 7,8,9. Our case contrasts with the above case reports in that our patient’s abdominal pain was chronic and not present on the day of her presentation.…”
Section: Discussioncontrasting
confidence: 63%
“…He underwent a simultaneous cholecystectomy and elective revascularization of his aortic and visceral occlusive disease. Other case reports present instances of acute acalculous cholecystitis in patients with critical illness causing systemic inflammation such as a severe infection, systemic lupus erythematosus, or burns 7,8,9. Our case contrasts with the above case reports in that our patient’s abdominal pain was chronic and not present on the day of her presentation.…”
Section: Discussioncontrasting
confidence: 63%
“…There are two morphological stages of G. duodenalis : a trophozoite and a cyst (infective stage). The parasite can colonize the upper small intestine but it was also found in the lower small intestine, stomach, colon and biliary tract [ 3 , 7 ]. G. duodenalis transmission occurs via fecal–oral route (from contaminated water or food and directly from infected individuals) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies showed gall bladder carcinoma to be the 6 th common cancer involving gastrointestinal system (Goodman and Wagman, 2010). Also, many parasites encounterred in Egypt cause acute cholecystitis, as malignant malaria (Abreu et al, 2013) ascariasis (Azhar et al, 2015), toxocariasis (Strickler et al, 2016) and giardiasis (Araki et al, 2017) as well as Staphylococcus saprophyticus, Corynebacterium urinapleomorphum, and Heliobacter pylori (Backert et al, 2018).…”
Section: Discussionmentioning
confidence: 99%